An evaluation of ride quality in lift systems of selected public high-rise buildings in Abuja, Nigeria - Ibrahim, Emmanuel Chongcicimmi; Stanley, Andrew Mhya; Mohammed Manzuma, Buhari; Ayeni, Olugbenga; Isah, Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ride quality of lifts enhances the comfort of lift users in high rise buildings. This work investigated the ride quality of lifts in selected high-rise buildings within the Central Business District (CBD) of Abuja, Nigeria. The study adopted field survey method. Instruments like the WT85 Digital Sound Level Meter and Smart Sensor Vibration Meter alongside a checklist were used for data collection on lift cabin interior sound level and vibration during acceleration. Results show that 64.3% of the buildings have unsatisfactory interior lift sound levels and 71.4% with poor ride quality. Inferential statistical analysis showed significant differences (p<0.05) in the mean values of lift car interior sound levels and lift acceleration values. The assessed lift systems were considered to have unsatisfactory ride quality as majority of them produced sounds beyond established standards for optimum sound level and vibration in lift cars (£55dBA and 1m/s2 ). For high-rise buildings considering modernization of lift systems or installation of new ones, ride quality is a factor to consider for optimum service delivery and users’ ride comfort. However, the findings from the study could be of benefit to lift consultants and manufacturers when planning for lift design and installation in high rise buildings.